Fumarole Alteration of Hawaiian Basalts: A Potential Mars Analog - Gerard, Teri; Mchenry, Lindsay J. (Proceedings of the Wisconsin Space Conference, 2012)
Over the last decade of Mars exploration, planetary scientists have discovered widespread sulfate-rich deposits indicating the acidic weathering of basalts (Squyres and Knoll, 2005; Bibring et al., 2006). By understanding the processes occurring during alteration of basalt in wet volcanic environments such as solfataras, we can learn more about the past aqueous processes on Mars. Chemically altered mineral assemblages of potentially hydrothermal origin have been detected at several Mars sites including Gusev Crater, Mawrth Vallis, and Nili Fossae (Ehlmann et al., 2010; Ehlmann et al., 2008; Chojnacki and Hynek, 2008; Schmidt et al., 2008; Yen et al., 2008; Bibring et al., 2006). The abundant magnesium and iron sulfates, hematite, and silica suggest alteration of basalts in water-limited, saline-acidic conditions, consistent with acidic evaporites or potentially sulfur-rich fumaroles (Squyres et al., 2007; Morris et al, 2000). In order to fully understand the formation of the minerals observed on Mars, it is necessary to fully understand the geochemical and mineralogical pathways that the basalt undergoes as it weathers under different conditions. Kilauea volcano Hawaii provides an excellent Mars analog for hydrothermal alteration. Samples collected at various fumaroles will be analyzed in order to determine any mineralogical and/or geochemical signatures that can help determine the origin of the mineral assemblages seen on Mars.Â